PERAN GURU DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Syaifulloh, Ahmad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2022)
Teachers have a crucial role in curriculum development. Because teachers are professionals, teachers are the gateway to innovation as well as the gateway to integrated development. This is because development can be carried out if it starts from developing people first. Without people who are capable, skilled, knowledgeable, intelligent, creative and responsible, integrated development will not be able to be implemented well. Therefore, every teacher and other education personnel must be able to understand the curriculum as well as possible. So that they can design, implement, control and evaluate curriculum development, because teachers are the main implementers of learning activities and directly interact with students who are expected to achieve competencies that can be a benchmark for the success of curriculum development. Through qualitative research methods and library research, this article tries to explain the role of teachers in developing the PAI curriculum. The results of this research show that there are four roles that teachers must play in developing the curriculum, namely: As a curriculum implementer; As a curriculum developer; As a curriculum adapter (aligner); and as a curriculum researcher.